Microstructure, mechanical and tribological properties of DLC/Cu-DLC/W-DLC composite films on SUS304 stainless steel substrates. (3rd May 2019) - Gu, Kunming; Zheng, Yi; Luo, Junxuan; Qin, Xiande; Yang, Xinge; Abbas, Nadeem; Tang, Jiaoning
Abstract: Besides their direct use as functional coatings, metal doped diamond-like carbon (Me-DLC) films are also adopted as buffer layers of DLC films to help reducing residual stress or improving adhesion to the substrates. However, single Me-doped buffer layer often deteriorates some of the inherent excellent mechanical properties of DLC films. In this paper, composite DLC films with double buffer layer based on W-DLC and Cu-DLC thin films were deposited on stainless steel (SS) substrates using microwave electron cyclotron resonance chemical vapor deposition (ECR-CVD) method combined with magnetron sputtering method, forming a film structure of DLC/Cu-DLC/W-DLC/SS. The composite films with this film structure show very smooth surface morphology, and possess high hardness (35 GPa) and low friction coefficient (0.14, friction pair: GCr15, HRC60) at the same time. It was also shown in this work that the sputtering current of the W target when depositing the most inner W-DLC layer can affect the formation of the sp 3 bond in the composite film, which has great influence on the mechanical properties of the composite films. With different sputtering current, the hardness of the composite films can go up to 35 GPa, or go down to 14 GPa, resulting in different wear resistance against GCr15 friction pair.